The barrier functions of crude cervical mucus plugs against HIV-1 infection in the context of cell-free and cell-to-cell transmission. (1st November 2021) - Mhlekude, Baxolele; Lenman, Annasara; Sidoyi, Phikolomzi; Joseph, Jim; Kruppa, Jochen; Businge, Charles Bitamazire; Mdaka, Mana Lungisa; Konietschke, Frank; Pich, Andreas; Gerold, Gisa; Goffinet, Christine; Mall, Anwar Suleman
Abstract : Objective: The cervical mucus plugs are enriched with proteins of known immunological functions. We aimed to characterize the anti-HIV-1 activity of the cervical mucus plugs against a panel of different HIV-1 strains in the contexts of cell-free and cell-associated virus. Design: A cohort of consenting HIV-1-negative and HIV-1-positive pregnant women in labour was recruited from Mthatha General Hospital in the Eastern Cape province of South Africa, from whom the cervical mucus plugs were collected in 6 M guanidinium chloride with protease inhibitors and transported to our laboratories at −80 °C. Methods: Samples were centrifuged to remove insoluble material and dialysed before freeze–drying and subjecting them to the cell viability assays. The antiviral activities of the samples were studied using luminometric reporter assays and flow cytometry. Time-of-addition and BlaM-Vpr virus-cell fusion assays were used to pin-point the antiviral mechanisms of the cervical mucus plugs, before proteomic profiling using liquid chromatography-tandem mass spectrometry. Results: The proteinaceous fraction of the cervical mucus plugs exhibited anti-HIV-1 activity with inter-individual variations and some degree of specificity among different HIV-1 strains. Cell-associated HIV-1 was less susceptible to inhibition by the potent samples whenever compared with the cell-free HIV-1. The samples with high antiviral potency exhibited a distinct proteomic profile when compared with the less potent samples. Conclusion: The crude cervical mucus plugs exhibit anti-HIV-1 activity, which is defined by a specific proteomic profile. Abstract : Supplemental Digital Content is available in the text